Bridging Faith and Finance: A Comparative Study of Sharia-Compliant Microfinance Performance Across West Java - Imam Safei Muslim (Sekolah Tinggi Agama Islam Kuningan, 2025)
Financial inclusion remains critical globally, with 1.4 billion adults lacking formal financial services. In Indonesia, 49% of adults remain unbanked, particularly in rural areas. Islamic microfinance institutions offer Sharia-compliant alternatives for Muslims avoiding conventional finance, yet limited empirical evidence exists on comparative performance across models regarding financial sustainability, social impact, and Sharia compliance. This study compares financial and social performance of Islamic microfinance models (BMTs, BPRS, Islamic cooperatives) across West Java, examines Sharia compliance adherence, and identifies key performance determinants including institutional characteristics and regional contexts. A comparative cross-sectional study across Western and Eastern West Java analyzed quantitative and qualitative data from representative samples. Financial metrics, social outreach indicators, and Sharia compliance measures were examined to identify performance determinants and regional disparities. Significant regional disparities emerged, with Western institutions demonstrating superior financial sustainability and outreach. Institutional age, staff capacity, and authentic Sharia compliance were key performance determinants. Dual-mission tension exists between financial sustainability and poverty outreach, with larger loans improving financial performance but potentially reducing poorest client focus. Findings provide empirical evidence on Islamic microfinance performance variations, emphasizing context-specific strategies, human capital development, and authentic Sharia governance importance for achieving both financial sustainability and social objectives in diverse regional settings.